AN ANALYSIS ON STUDENTS’ ERROR IN WRITING SIMPLE SENTENCES (THE DESCRIPTIVE QUALITATIVE STUDY OF THE SECOND SEMESTER Of ENGLISH EDUCATION DEPARTMENT STUDENTS AT IAIN KEDIRI IN THE ACADEMIC YEAR Of 2017/2018) - Fitriatul Masitoh (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2019)
This study explores kinds of errors that the English education department students of the second semester make in writing simple sentences and to examine the most frequent errors they make. Related to this issue, descriptive qualitative method was implemented in this study. The result shows that the second semester students, C class, of English education department made errors in writing simple sentences especially in narrative text. The errors found are 212 errors. They made errors covering all four kinds of errors. They are omission, addition, misformation, and misordering. The misformation errors have the highest number of errors. There are 102 numbers of errors or 48,11% of the total errors. On the other hand, the lowest error is misordering. There are only 12 errors or 5,66% of the total number of error.